A New Proposal for Learning Curve of TEP Inguinal Hernia Repair: Ability to Complete Operation Endoscopically as a First Phase of Learning Curve. (23rd April 2014) - Hasbahceci, Mustafa; Basak, Fatih; Acar, Aylin; Alimoglu, Orhan
Abstract : Background . The exact nature of learning curve of totally extraperitoneal inguinal hernia and the number required to master this technique remain controversial. Patients and Methods . We present a retrospective review of a single surgeon experience on patients who underwent totally extraperitoneal inguinal hernia repair. Results . There were 42 hernias (22 left- and 20 right-sided) in 39 patients with a mean age of 48.8 ± 15.1 years. Indirect, direct, and combined hernias were present in 18, 12, and 12 cases, respectively. The mean operative time was 55.1 ± 22.8 minutes. Peritoneal injury occurred in 9 cases (21.4%). Conversion to open surgery was necessitated in 7 cases (16.7%). After grouping of all patients into two groups as cases between 1–21 and 22–42, it was seen that the majority of peritoneal injuries (7 out of 9, 77.8%, P = 0.130 ) and all conversions (P = 0.001 ) occurred in the first 21 cases. Conclusions . Learning curve of totally extraperitoneal inguinal hernia repair can be divided into two consequent steps: immediate and late. At least 20 operations are required for gaining anatomical knowledge and surgical pitfalls based on the ability to perform this operation without conversion during immediate phase.